Analisis Distribusi Debit Aliran pada Pelimpah dengan Variasi Model Bangunan Peluncur - Satria Dilaga; Yudi Hardiansyah; Fauzan Hamdi; Andi Bunga Tongeng (CV. Gio Architect, 2023)
Spillway is a structure in a dam designed to drain excess water into a downstream river. The purpose of this study was to determine the water level in the stepped and ladderless chutes and to determine the type of flow that occurs in the stepped and non-stepped chutes. The research method is a laboratory experiment and the data obtained is based on the results of observations made at the Hydraulics Laboratory of the University of Muhammadiyah Makassar. After passing through the launcher building, the water level in the 1st aperture ladder launcher is 2.7 cm, 2.9 cm in the 2nd opening, 2.9 cm in the 3rd opening. The water level in the ladderless launcher at the 1st opening is 3 cm, at the second opening is 3.5 cm, at the 3rd opening is 3.9 cm so that it can be concluded that the shape of the launcher structure influences the water level, thus the water level at ladderless launcher is larger than ladderless launcher. After passing through the launcher building, the Reynolds number on the stepped launcher with the 1st opening is 8301, on the 2nd opening is 8811, on the 3rd opening is 9061. to 3 of 26,103.